Hybrid surgery for aneurysm of the arch and descending part of the aorta. Right-left subclavian bypass as a variant of subtotal debranching - O.V. Zelenchuk; A.V. Khokhlov; A.Yu. Shkandala; K.S. Boiko; O.Yu. Polishchuk; Z.V. Press; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The article presents the experience of our team in various surgical methods of treating aortic pathology. Surgical pathology of the thoracic aorta, namely aneurysms and dissections, remains controversial for the «heart team». In recent years, endovascular aortic replacement (TEVAR) has proven itself as a treatment option for many aortic diseases with a mortality rate up to 7.5 %. According to the latest clinical recommendations, TEVAR has become the method of choice in the treatment of acute aortic dissection, showing better results compared to medical therapy and open surgery. However, the endovascular approach requires certain anatomical features that allow the correct placement of the stent-graft, which is not always possible. Thus, when the brachiocephalic arteries are involved in the pathological process, artificial blood circulation is required with the use of additional methods to protect the brain, such as cerebral perfusion and hypothermia. All these factors increase the risk of intra- and postoperative complications, as well as early mortality. Different methods of open surgery to replace all or most of the thoracic aorta are described, which represent a radical approach and require a high level of professional skills of the surgeon and experience in working with artificial blood circulation.